2013
DOI: 10.2217/nnm.13.132
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Nanofiber Scaffolds for Orthopedic Tissue Repair and Regeneration

Abstract: This article reviews recent significant advances in the design of nanofiber scaffolds for orthopedic tissue repair and regeneration. It begins with a brief introduction on the limitations of current approaches for orthopedic tissue repair and regeneration. It then illustrates that rationally designed scaffolds made up of electrospun nanofibers could be a promising solution to overcome the problems that current approaches encounter. The article also discusses the intriguing properties of electrospun nanofibers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 120 publications
(108 reference statements)
0
53
0
Order By: Relevance
“…The mechanical properties of electrospun nanofiber mats can be tailored by varying the composition using different types of polymers and polymer blends, and by adjusting the size of individual nanofibers [35]. The Young's modulus of nanofiber mats was determined from the slope of the linear region of stress-strain curve [36].…”
Section: Mechanical Properties Of Nanofibersmentioning
confidence: 99%
“…The mechanical properties of electrospun nanofiber mats can be tailored by varying the composition using different types of polymers and polymer blends, and by adjusting the size of individual nanofibers [35]. The Young's modulus of nanofiber mats was determined from the slope of the linear region of stress-strain curve [36].…”
Section: Mechanical Properties Of Nanofibersmentioning
confidence: 99%
“…The values are different from those obtained in equivalent bulk materials [27]. Indeed for fibre-based materials, the mechanical properties are affected by the polymer molecular weight, morphology, crystallinity, as well as the material size and shape such as porosity, pore area and fibre size, density and orientation [44]. For instance, when electrospun fibre-based materials are developed with aligned fibres, the modulus and the tensile strength increase and the mechanical behaviour becomes anisotropic in comparison to randomly arranged fibres [62,63].…”
Section: Propertiesmentioning
confidence: 74%
“…The potential medical applications are in the development of scaffolds for tissue engineering, carriers of bioactive compounds and cells, and in wound dressings. Additionally, in-terms of positively promoting cell-polymeric matrix interactions, the high surface area of the nanostructured, nanofibrous scaffolds allows for oxygen permeability and provides sufficient space for nutrient and waste exchange [44]. Moreover, in wound dressings, fluid accumulation at the wound site is limited and the material pore size prevents bacterial penetration.…”
Section: Polymeric Nanofibres and Nanofibrous Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alignment of polymer backbone structures along fiber axes forms crystal domains [150][151][152], which have provided a foundation for optoelectronics such as nanofiber light sources with color tunability and waveguide capabilities and nanofiber lasers [39,146,148,. Biologically, hybrid nanofiber scaffolds have provided a cell niche conducive to improved attachment, proliferation, and cell differentiation [190][191][192][193][194][195][196][197][198], as well as targeted drug delivery carriers [198][199][200][201][202][203][204][205][206]. Filtration using ONFs [207] equipped with activated carbon has revealed adsorption of volatile organic compounds (VOCs) present in the air [208][209][210], and Scholten et al reported that adsorption and desorption of VOC by electrospun nanofibrous membranes (ENMs) were faster than that of conventional activated carbon [208].…”
Section: Organic Micro-and Nano-fiber Systemsmentioning
confidence: 99%